Uji Kualitas Kertas Seni Dari Alang-Alang Melalui Proses Organosolv Dengan Konsentrasi Pelarut Dan Lama Pemasakan Yang Berbeda - Syalala, Yoni, Dra. Aminah Asngad , M.Si (2017)
Art paper as a means of creativity that many people interested in because of the texture and colors are unique and interesting. Art paper is usually made of wood fibers or plants that have high fiber content. Reeds is a plant that can be used as a basic material for making art paper because it has high cellulose content. The purpose of this research is to know the quality test art paper from cogon grass the results of the treatment concentration ethanol and time cooking. This research uses experimental method with Completely Randomized Design (RAL) factorial design, with 3 repetitions. The factor 1 is the concentration of ethanol (K), K1 (30%), K2 (40%), K3 (50%) and factor 2 that is cooking time (L), L1 (60 min), L2 (90 min). The results showed art paper with the highest tensile strength and tear strength in the K3L1 threatment (50% ethanol concentration and 60 minutes cooking time) with 1.53 N/mm2 for tensile strength and 2,37 N/mm2 for tear strength. The sensory test results show that te highest average value given by the panelists on the art paper texture is 1.90 (very rough) in the K3L1 treatment, the assessment of the fiber appearance is 1.85 (highly visible) in the K3L1 treatment, the color assessment is 1.65 (old cream) on the K3L1 treatment, and the assessment of the receiving power was 0.50 (very like) on the K1L2 treatment